Osteoporosis and obesity in the South East of Caspian Seashore and its relationship to osteoporosis prevalence in Iran - Majid Malekzadeh Shafaroudi; Nourollah Rezaei; Behrooz Mohammadnegad; Gholamali Usefi; Ali Malekzadeh Shafaroudi (Babol University of Medical Sciences, 2024)
Background: Osteoporosis is the most common metabolic bone disease that begins with a decrease in bone mass and deterioration in the micro-architecture of the bone tissue, making the bones thinner and susceptible to fragility. A comprehensive estimation of the prevalence of osteoporosis in provinces of Iran seems to be necessary. Methods: This study was a descriptive-analytical study. The study population included 518 people aged 30-65 years including 297 males and 221 females to measure their bone density. The data collection method was through BMD measurement using Dual-Energy X-ray Absorptiometry (DXA) method. All obtained data stored in the SPSS-16 database and statistically analyzed. The data analyzed using analytical, statistical methods. The significance level of the test was considered to be P≤0.05. Results: In the present study, according to BMI status, 45.2% of the patients were obese, 38.2% were overweight. Despite the general belief that increasing in weight can be associated with an increase in bone mass, the present research revealed that nearly 35.9% of the research population, suffered obesity and osteoporosis at the same time. Metargression analysis of data from different studies have illustrated that changing in frequency of osteoporosis as an oriented change in prevalence of osteoporosis from west to east and south to north (P≤0.05) Conclusion: Iran society is under concern to more osteoporosis in the coming years at young and old ages which doubled with severe decline in growth rate of population from 3.7% to 0.63% in 2022. This can increase older people ratio over 30% in 2050.